Navigasi Strategis Perencanaan Kurikulum di UIN KH Abdurrahman Wahid: Inovasi Manajemen Pendidikan Era Digital - Sabrina Ais Zahra; Mutammam Mutammam (Lembaga Yasin AlSys, 2026)
Curriculum planning is a strategic aspect of educational management that determines the direction of graduate competency development in the digital era. Islamic Religious Higher Education institutions are required to integrate Islamic values with developments in science and technology in order to remain relevant to the needs of society and the world of work. This study aims to analyze the curriculum planning model at UIN K.H. Abdurrahman Wahid Pekalongan in facing the challenges of digital transformation without neglecting Islamic values. This study used a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation study. The main informant of the study was the Head of the Islamic Religious Education (PAI) Study Program at UIN K.H. Abdurrahman Wahid Pekalongan. The results show that curriculum planning is carried out participatively by involving university leaders, lecturers, students, alumni, graduate users, and quality assurance institutions through needs analysis, discussion forums, workshops, curriculum mapping, and continuous evaluation. The curriculum is designed based on the vision of integrating Islam, science, and technology and accommodates the strengthening of digital literacy, religious moderation, professional competence, and the use of Artificial Intelligence (AI)-based technology. Nevertheless, the implementation of the digital curriculum still faces constraints in the form of limited technological infrastructure, internet bandwidth, and the digital literacy of some lecturers. The conclusion of this study affirms that the success of curriculum planning at UIN K.H. Abdurrahman Wahid Pekalongan is determined by the institution’s ability to integrate Islamic values, technological innovation, and continuous evaluation. The implications of this study contribute to the development of a curriculum planning model for Islamic Religious Higher Education that is adaptive to digital transformation and oriented toward producing graduates who are competent, adaptive, and characterized by strong values.